History of Computer supported Teaching and Learning in Hungarian Public Education (Training and Practice : Journal of Educational Sciences, 2017)
The history of Computer-supported Teaching and Learning goes back about forty years in Hungarian Public Education. Several ICT development projects took place in Hungary during the last three and a half decades, financed either by govermental (for example Sulinet, TÁMOP, HEFOP, TIOP) or other sources (Phare, Soros Foundation Public Education Development Programme etc.). The task which we have set ourselves in this paper is to present this expansion in chronological order. We hope that data collected by our research team and presented here provides a starting point for further research and discussion.